Автоматизація складських процесів на підприємстві - Огоновська, Ірина; Думанський, Нестор (Видавництво Львівської політехніки, 2018)
The article describes the important role of warehouse space in the enterprise. The program products are described with the help of which it is possible to automate warehouse processes and optimize work at the enterprise.
Keywords: автоматизація; склад; складські процеси; підприємство; програмні продукти